The greatest : Muhammad Ali - Myers, Walter Dean, 1937- (New York : Scholastic Press, 2001)
Describes Ali's childhood, his rise as a champion, his politics, his beliefs, and his battle against Parkinson's disease.
Includes bibliographical references (p. 164) and index.
RL5.
12 and up.
1030
Accelerated Reader AR
Maine Student Book Award list, 2002-2003
Keywords: Ali, Muhammad, -- 1942- -- Juvenile literature; Boxers (Sports) -- United States -- Political activity -- Juvenile literature; Vietnam War, 1961-1975 -- Conscientious objectors -- Juvenile literature; Boxers (Sports) -- United States -- Biography -- Juvenile literature